Colonoscopy screening and surveillance guidelines. Issue 4 (3rd May 2021) - Saito, Yutaka; Oka, Shiro; Kawamura, Takuji; Shimoda, Ryo; Sekiguchi, Masau; Tamai, Naoto; Hotta, Kinichi; Matsuda, Takahisa; Misawa, Masashi; Tanaka, Shinji; Iriguchi, Yosuke; Nozaki, Ryoichi; et al.
Abstract : The Colonoscopy Screening and Surveillance Guidelines were developed by the Japan Gastroenterological Endoscopy Society as basic guidelines based on the scientific methods. The importance of endoscopic screening and surveillance for both detection and post‐treatment follow‐up of colorectal cancer has been recognized as essential to reduce disease mortality. There is limited high‐level evidence in this field; therefore, we had to focus on the consensus of experts. These clinical practice guidelines consist of 20 clinical questions and eight background knowledge topics that have been determined as the current guiding principles.